IMPLEMENTASI KOLABORASI KAMPUNG ADAT DAN PEMERINTAHAN DI KAMPUNG ADAT KAITEMUNG DISRTIK NIMBORAN KABUPATEN JAYAPURA - Waicang Rode (Universitas Cenderawasih, 2020)
The provinces of Papua and West Papua have a wealth of cultural characteristics ranging from language to customary institutions that are formed within each cultural tribe. Customary institutions in Papua are known as institutions that play an important role in assisting development issues, both regional development and Papuan people. Therefore, the regional government of Papua Province, especially the Regional Government of Jayapura Regency, is in order to improve the synergy of services between the two institutions in one management to the community, especially indigenous peoples in the Jayapura Regency area. The Jayapura Regency Government emphasizes this, in a collaboration model between the two institutions, resulting in synergy between customary institutions and the government. The collaboration model of the two institutions is outlined in the Jayapura Regency Regional Regulation number 8th of 2016 concerning Traditional Village. This customary village development program has received a good response, among the indigenous people of Nambulong, especially the indigenous people of Kampung Ketemung, which is in the area of the Grime nature reserve area. Since 2007 the Adat institution of Ketemung village began to build traditional houses with the independent of the indigenous people, then in 2014 the Regent of Jayapura officially declared Kampung Ketemung as a Traditional Village, which was marked by the laying of the first roof by the Regent of Jayapura. This research study aims to see how the collaboration model between the two institutions, as well as the factors that influence the implementation of the policy, both supporting factors and inhibiting factors. In transferring information about this research, the researcher uses three methods, namely observation, interviews and documentation. The results of this study show that the collaboration model in the Ketemung Traditional Village has been seen in the bureaucratic structure and also the activities carried out in the village, whether it is indigenous women's activities, education to deliberation activities However, in running the governance of the Ketemung Ondoafi Traditional Village, there are many challenges both from the previous village government and from the current head of government. Therefore in this study the researcher suggests that the Jayapura Regency government be made a legal basis that guarantees ondoafi in carrying out the presentation. ntahan in collaboration with the government.